Wrapped Staring Spotlight SAR - Mittermayer, Josef; Kraus, Thomas; Lopez-Dekker, Paco; Prats-Iraola, Pau; Krieger, Gerhard; Moreira, Alberto (IEEE Transactions on Geoscience and Remote Sensing, 2016)
This paper proposes the wrapped staring spotlight (WSS) SAR imaging mode, which is a new method to extend the azimuth steering capability for phased array SAR to achieve either an improved azimuth geometric or radiometric resolution. It investigates the utility of steering directions with main lobe gains that are smaller than that of the grating lobes and exposes how these directions can be exploited. Furthermore, two methods are proposed to reduce the speckle and the image noise at once, i.e., the Look-Normalized Pattern Correction and the Ω-weighting. Based on two example TerraSAR-X WSS acquisitions, the image performance of extended and point targets is discussed.
DLR Import::2019-04-02
Keywords: Look-Normalized Pattern Correction (LNPC); synthetic aperture radar (SAR); wrapped staring spotlight (WSS); Ω-weighting